Assessment of the Frequency of Different Patterns of Clinical Presentation of Children Presenting with Congenital Adrenal Hyperplasia - Muhammad Hamza, Feezan Raza, Moqeet Hayat, Attaullah Bangulzai, Syed Aqeel Akbar Shah Gillani, Murtaza Jaffar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Congenital suprarenal hyperplasia is an autosomal recessive condition that is characterized by defects in some of the 5-enzymes required for cortisol synthesis. Literature indicates a high incidence of salt depletion and genital virilization in children with congenitally adrenal hyperplasia. The purpose of this study was to examine the prevalence of clinical patterns in children with congenital adrenal hyperplasia. Material and methods Study design: Cross sectional study Setting: Department of Pediatric, Fatima Memorial Hospital, Lahore. Duration: 6 months i.e. 19-12-2019 to 18-06-2020 Data collection: 92 infants who met the inclusion criteria were included in the study. Blood sample was obtained, if serum sodium was <135mEq/L, salt depletion was labeled. Then, genital examination for assessment of genital virilization was done. All data was entered in specially designed Performa and analyzed in SPSS. Results: The mean age of patients was 6.52±3.56 months. There were 49 (53.26%) male while 43 (46.74%) female infants. The mean weight of patients was 5.59±1.44 kg. There were 21 (22.83%) cases of consanguineous marriage while 71 (77.17%) were others. 63 (68.48%) had salt depletion while 29 (31.52%) did not had salt depletion. 39 (42.39%) patients had genital virilization while 53 (57.61%) did not have genital virilization. Conclusion: The frequency of patterns (salt depletion and genital virilization) of Congenital adrenal hyperplasia are high in local population.